Students’ Error Analysis in Constructing Negative and Interrogative Sentence in Simple Present Tense - Hasyim, Ruslan; Tahang, Heriyanti; Dimara, Oktovianus Deram (JLE: Journal of Literate of English Education Study Program, 2023)
The aim of this research is to analyze and to identify kinds of errors made by students of Junior High School in constructing negative and interrogative sentences in simple present tense. This research used comprehensive literature review from various source. By the result, it is informed the proportion of students’ simple present error in constructing interrogative sentence based on surface strategy taxonomy, the percentage omission is 80.9%, addition is 0.20%, misformation is 0,47%, and misordering is 0.62%. so that the most common error committed by the students in constructing negative and interrogative sentence is omission error. The finding of this research provide a literature for English teachers and also for students, should pay more attention to writing teaching and learning process and also stress on the material in which difficult for the students. They may use a new method in teaching learning process especially in teaching grammar about simple present tense .